Analysis Of Student Error In Writing Descriptive Text - Fatimah Azzahra Siregar; Afrohul Fadhillah Batubara; Cut Ria Manisha (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This research aims to analyze the errors made by students in writing descriptive texts. The study employed a descriptive qualitative research method and involved 12 students from the Department of English Education at UINSU as research participants. Data was collected through documentation, specifically gathering 12 descriptive texts written by the students. The results of the analysis indicate common errors in descriptive writing, with punctuation errors comprising the largest percentage at 33%. Students often struggle with proper punctuation usage, leading to unclear sentence structures. Word choice errors were the second most prevalent at 13%, reflecting challenges in selecting appropriate and accurate words for descriptions. Additional significant errors included word order (12%), tense agreement (12%), capitalization (6%), verb form (6%), verb tense (6%), and pronoun agreement (6%). Less common errors were observed in article usage (3%) and spelling mistakes (3%). These findings emphasize the areas that require attention and improvement for students to enhance their descriptive writing skills.